The role of protein arginine deiminase 4-dependent neutrophil extracellular traps formation in ulcerative colitis - Wang, Ping; Liu, Dan; Zhou, Ziqi; Liu, Fangjun; Shen, Yiming; You, Qi; Lu, Shiping; Wu, Jie (Frontiers in Immunology, 2023)
Neutrophil extracellular traps (NETs) play an important role in the development and progression of ulcerative colitis (UC). Peptidyl arginine deiminase type 4 (PAD4) is essential for the formation of NETs via catalyzing histone citrullination. To explore the role of PAD4-mediated NETs in intestinal inflammation of dextran sulfate sodium (DSS)-induced UC, acute and chronic colitis mouse models were established by supplementing DSS in drinking water. Colon tissues from colitis mice were analyzed for the level of PAD4 expression, citrullinated histone H3(Cit-H3), intestinal histopathology, and inflammatory cytokines secretion. Serum samples were tested for systemic neutrophil activation biomarkers. Colitis mice administered with Cl-amidine, a PAD4 inhibitor, and PAD4 knockout mice were investigated to detect NETs formation, intestinal inflammation, and barrier function. We found the formation of NETs significantly increased in DSS-induced colitis mice and was correlated with disease markers. Blocking NETs formation by Cl-amidine or PAD4 genetic knockout could alleviate clinical colitis index, intestinal inflammation, and barrier dysfunction. Therefore, this study provided a research basis for the role of PAD4-mediated NETs formation in the pathogenesis of UC and suggested that inhibition of PAD4 activity and the formation of NETs may be helpful for the prevention and treatment of UC.